Early-Onset Aicardi-Goutières Syndrome: Magnetic Resonance Imaging (MRI) Pattern Recognition. (September 2015) - Vanderver, Adeline; Prust, Morgan; Kadom, Nadja; Demarest, Scott; Crow, Yanick J.; Helman, Guy; Orcesi, Simona; Piana, Roberta La; Uggetti, Carla; Wang, Jichuan; Gordisch-Dressman, Heather; van der Knaap, Marjo S.; et al.
Aicardi-Goutières syndrome is an inherited leukodystrophy with calcifying microangiopathy and abnormal central nervous system myelination. As fewer diagnostic computed tomographic (CT) scans are being performed due to increased availability of magnetic resonance imaging (MRI), there is a potential for missed diagnoses on the basis of calcifications. We review a series of patients with MRIs selected from IRB-approved leukodystrophy biorepositories to identify MRI patterns for recognition of early-onset Aicardi-Goutières syndrome and scored for a panel of radiologic predictors. Each individual predictor was tested against disease status using exact logistic regression. Features for pattern recognition of Aicardi-Goutières syndrome are temporal lobe swelling followed by atrophy with temporal horn dilatation, early global cerebral atrophy and visible calcifications, as evidenced by 94.44% of cases of Aicardi-Goutières syndrome correctly classified with a sensitivity of 90.9% and specificity of 96.9%. We identify a panel of MRI features predictive of Aicardi-Goutières syndrome in young patients that would differentiate it from other leukoencephalopathies.